Roman Law and the Idea of Europe - Tuori, Kaius; Björklund, Heta (Europe's Legacy in the Modern World, 2019)
Roman law is widely considered to be the foundation of European legal culture and an inherent source of unity within European law. Roman Law and the Idea of Europe explores the emergence of this idea of Roman law as an idealized shared heritage, tracing its origins among exiled German scholars in Britain during the Nazi regime. The book follows the spread and influence of these ideas in Europe after the war as part of the larger enthusiasm for European unity. It argues that the rise of the importance of Roman law was a reaction against the crisis of jurisprudence in the face of Nazi ideas of racial and ultranationalistic law, leading to the establishment of the idea of Europe founded on shared legal principles. With contributions from leading academics in the field as well as established younger scholars, this volume will be of immense interests to anyone studying intellectual history, legal history, political history and Roman law in the context of Europe.